VIDEO-BASED DATA UTILIZATION FOR THE DEVELOPMENT OF HIGH FREQUENCY DEFORMATION OBSERVATION METHODS FOR BRIDGE STRUTH DEFORMATION ANALYSIS - Candika Alamsyah, Dimas
The close range photogrammetry (CRP) method based on digital video observation data using a non-metric camera on a device, is one method that is considered to have the potential to be used in observing high-frequency deformation, it is based on three main factors, namely easy application, economical costs, as well as being able to provide data samples with very dense temporal scales. In this study, the video-based Close range photogrammetry (CRP) method using a non-metric camera was used to detect movement or high-frequency deformation in the research study area of the Cxxx bridge which focused on observing the bridge strut. This study found that observations using video with the CRP processing method were proven to be able to produce data with high frequency, as evidenced by the amount of data as much as 8,737 that could be generated from an observation time of 4.85 minutes. accuracy of 2.4 cm for the horizontal component and 1.3 cm for the vertical component. In this experiment, it was also found that there was a dynamic change of the object during the observation with the maximum change value for the horizontal component of 4.3 cm and 1.3 cm for the vertical component with respect to the long (y) and cross (x) orientation of the bridge.